The role of the antennae in the compass-based orientation of the equatorial sandhopper Talorchestia martensii Weber (Crustacea Amphipoda). Issue 4 (4th July 2021) - Ugolini, Alberto; Nistri, Annamaria; Agnelli, Paolo; Ciofini, Alice; Wilcockson, David C.
Abstract : The equatorial sandhopper Talorchestia martensii uses the sun, the moon and the natural magnetic field as orienting compass references. In some arthropod species, the antennae are important for time compensated solar orientation. Therefore, we evaluated the role of antennae in solar, lunar and magnetic compass orientation in T. martensii . We released intact and antennaeless individuals in a Plexiglas bowl in the dark, and under the sun or moon, with and without the horizontal component of the magnetic field and recorded their orientation. For the tests under the moon, sandhoppers were released in conditions of modest azimuthal speed (10–15°/hr) and high azimuthal speed (≈ 59°/hr) of the moon. No significant difference in the orienting behaviour between antennaeless and intact individuals was observed. Therefore, the antennae do not seem to be involved in the sun or moon compass mechanisms of T. martensii . The photopositive responses showed by individuals released under high azimuthal speed of the moon and with the horizontal component of the magnetic field zeroed, indicate that the moon is probably not used as a chronometric compass reference in this species because of the variations in its azimuthal speed. This suggests a mechanism of photomenotaxis and therefore, a difference from sandhoppers from temperate latitudes that use a moon compass.